Effect of head impacts and chemical irritation on elite athletes` olfaction - Manninen, I.-K.; Mäkinen, L. K.; Laukka, P.; Klockars, T.; Blomgren, K. (European Journal of Sport Science, 2023)
Limited research exists on athletes` olfaction. As diet is an elementary part of an athlete`s lifestyle and training, it is important to know whether the sport discipline itself carries a risk for olfactory impairment. The aim of this study was to evaluate whether elite swimmers (chemical irritation), boxers (head impact) or soccer players (head impact) are at risk for impaired olfaction. Elite-level male swimmers (n=30), boxers (n=35) and soccer players (n=30) aged 18-40 years were recruited from Finnish sport clubs. Floorball players (n=30) were recruited as a control group. All participants filled in a questionnaire about their training history, nasal and sinonasal diseases, asthma, nasal operations and traumas, smoking and self-evaluation of olfaction and taste function. Sniffin` Sticks odour identification test with 12 different odorants and anterior rhinoscopy were performed on all participants. The mean score from the smelling test did not differ between the sport groups. Sinonasal diseases and bronchial asthma were more common among swimmers than among the other athletes. Rhinitis symptoms were common among all athletes. Boxing, soccer or swimming does not seem to affect sense of smell. The majority of our participating elite athletes had normal olfaction, even if they had had a long history of active sports.